Analisis Fenomenologis Pesan Dakwah Digital PCNU Pamekasan - Muhammad Ahnu Idris (LP2M IAI Miftahul Ulum Pamekasan, 2022)
The strong influence of social media in the lives of Indonesian people, requires preachers –both personal and institutional – to participate in filling this virtual world. Dai-dai arerequired to be able to use social media as a medium for delivering da'wah messages in aneffort to spread religious values. This da'wah model was later called